1986
DOI: 10.1029/jd091id12p13113
|View full text |Cite
|
Sign up to set email alerts
|

Ozone in the boundary layer of the equatorial Pacific Ocean

Abstract: Shipboard (∼7 m) ozone measurements made in the equatorial Pacific Ocean between 20°N and 17°S and 140°–160°W confirm the existence of a distinct ozone minimum in the vicinity of the equator in the late spring, its decline in the summer, and its absence in autumn. This minimum could not be correlated with high biological activity in surface waters. Coincident aircraft measurements of ozone from near sea surface (50–100 m) to 2 km in altitude were made along 150°W at stations at 10°N, 0°, 5° and 12°S in May–Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…The general MBL balance was nonetheless established as the result of entrainment of ozone rich air aloft, or large scale horizontal advection into the tropics from higher latitudes, balanced by net photochemical destruction throughout the day along with continuous, gradual dry deposition to the ocean. This pattern has been observed and explained thusly in numerous experiments since (Piotrowicz et al 1986;Johnson et al 1990; Thompson et al 1993;Heikes et al 1996;Singh et al 1996;Faloona et al 2005). Liu et al (1983) found a net ozone photochemical loss rate of 2 ppv day The source of ozone entrained into the remote MBL is from broad regions of tropospheric subsidence in conjunction with direct injection from the stratosphere and/or net in-situ photochemical production due to NO x from lightning, biomass burning, and/or lofted fossil fuel emissions Staudt et al 2003).…”
Section: Introductionmentioning
confidence: 94%
“…The general MBL balance was nonetheless established as the result of entrainment of ozone rich air aloft, or large scale horizontal advection into the tropics from higher latitudes, balanced by net photochemical destruction throughout the day along with continuous, gradual dry deposition to the ocean. This pattern has been observed and explained thusly in numerous experiments since (Piotrowicz et al 1986;Johnson et al 1990; Thompson et al 1993;Heikes et al 1996;Singh et al 1996;Faloona et al 2005). Liu et al (1983) found a net ozone photochemical loss rate of 2 ppv day The source of ozone entrained into the remote MBL is from broad regions of tropospheric subsidence in conjunction with direct injection from the stratosphere and/or net in-situ photochemical production due to NO x from lightning, biomass burning, and/or lofted fossil fuel emissions Staudt et al 2003).…”
Section: Introductionmentioning
confidence: 94%
“…As shown in Table 1, the annual mean background O 3 over China shows a spatial gradient from 33.7 ppb in the South China to 23.5 ppb in the Northeast/North China. Compared with that of the mid-or high latitudes, tropospheric O 3 at low latitudes (e.g., in the tropical region) is found to be lower as a result of the inactivity of the stratospheric and tropospheric transport (Piotrowicz et al, 1986) and the low photochemical formation due to the lack of precursor sources in the large oceanic areas (Chan et al, 1998;McFarland et al, 1979).…”
Section: Ambient O 3 and No X Concentration Throughout Chinamentioning
confidence: 99%
“…In contrast, in the marine boundary layer where concentrations of NOx are low ozone is destroyed (Singh et al, !996). Indeed extremely low concentrations of ozone (1-5ppbv) have been observed in the marine boundary layer of the equatorial Pacific (Singh et al, 1996;Piotrowicz et al, 1986). Such air can be pumped into the upper troposphere by deep convection, leading to low concentrations at high altitudes.…”
Section: Introductionmentioning
confidence: 99%